Evidence based rehabilitation in chronic pain syndromes [Kronik aǧri sendromlarinda kantita dayali rehabilitasyon] - (:unkn) unknown (My University, 2012)
Chronic pain syndrome (CPS) is a complex condition that presents a major challenge to physicians because of its unknown etiology and poor response to all kinds of therapies. It has been suggested that chronicity should be considered when pain persists longer than the acceptable healing time. The impact of chronic pain on patients' lives varies from minor limitations to complete loss of independence. The rehabilitation in CPSs is multi-disciplinary and involves physical, occupational, and manual therapy, aquatherapy, cognitive/behavioral therapy, biofeedback, psychotherapy, and some new therapies. In recent years, the point of view in chronic pain management has changed substantially and CPS is managed best with a multidisciplinary approach, including a rehabilitative process. The treatment protocol should be planned and modified individually. A combination of several methods has been tried, but long-term evidence-based studies are needed for new treatment modalities.
Keywords: Chronic pain syndromes; New rehabilitative methods; Pain rehabilitation